Acceptance for a booster dose of COVID-19 vaccine in Indonesia: A follow-up study - Harapan, Harapan; Maelani, Imelda; Anwar, Samsul; Latief, Kamaluddin; Mellinia, Sania A.; Nanda, Cut M.; Nainu, Firzan; Nirwana, Aura; Aksa, Rahmad; Sarifuddin, Sarifuddin; Astri, Yesi; Fathima, Raisha; Nalapraya, Widhy Y.; Ikram, Ikram; Mutiara, Suci; Syahraini, Aigia; Mudatsir, Mudatsir (Narra J, 2025)
The coronavirus disease 2019 (COVID-19) vaccination program in Indonesia has been implemented as a key strategy to mitigate the spread of the virus within communities. The success of this program depends on public acceptance of COVID-19 vaccines, including booster doses. The aim of this study was to assess the acceptance of the COVID-19 booster dose in Indonesia and to identify factors influencing individuals' acceptance. A cross-sectional study was conducted across 34 provinces in Indonesia on June 2023. Logistic regression analysis was used to identify the factors associated with booster dose uptake. The findings revealed that 88.8% (2,049/2,308) of respondents were willing to receive a booster dose if provided free of charge by the Indonesian government. However, acceptance decreased to 61.7% when respondents were informed of a 20% likelihood of side effects, even with a reported 95% vaccine efficacy. Adjusted logistic regression analysis identified ten significant factors associated with booster dose acceptance: sex, age, religion, history of previous COVID-19 infection, type of primary vaccine received, belief in vaccine-related conspiracy theories, trust in traditional medicine conspiracies, confidence in natural immunity, perceived vaccine efficacy, and perceived vaccine effectiveness. These findings suggest that acceptance of COVID-19 booster doses in Indonesia is influenced by intrinsic and extrinsic factors, including limited knowledge of booster dose benefits and concerns about potential side effects. To enhance public acceptance, targeted health campaigns and educational initiatives should be intensified, emphasizing the safety, efficacy, and importance of booster vaccinations in controlling the COVID-19 pandemic.